A Coupled Grid-Particle Method for Fluid Animation on GPU. (23rd May 2020) - Zhang, Fengquan; Wei, Qiuming; Wu, Zhaohui
Abstract : In digital production environments, high-quality visual effects play a key role in our mobile device such as game and film. The simulation of fluid animation with free surface is an important area in computer graphic. However, the tracking of fluid surface is a challenging problem because of its instability. In this paper, a coupled grid-particle method for fluid animation surface tracking and detail preserving is proposed. Firstly, based on the nonequilibrium extrapolation method, we design a novel method for reconstructing distribution functions (DFs) of interface grids of lattice Boltzmann method (LBM) and couple the reconstruction method with LBM and volume of fluid (VOF) to track the free surface, which can obtain the accurate surface. Secondly, in order to avoid the loss of details caused by weaknesses in the traditional LBM-VOF method, we design a coupled grid-particle method that not only makes full use of the advantages of the coupled grid-particle method but also realizes the two-way coupling between grid method and particle method. Furthermore, for achieving the real-time requirements of fluid animation, we use GPU parallel computing to accelerate the simulation and use an improved screen space fluid (SSF) rendering method for realistic rendering. The various experiments show that this work can track the fluid surface with high precision and preserve the details of the fluid surface, and it also achieves good real-time performance in large-scale fluid simulation.